MALAYSIAN SUKUK: ISSUES IN ACCOUNTING STANDARD - Abd Sukor, Mohd Edil (Jurnal Syariah, 2008)
There is a high demand and need for developing alternatives to the traditional debt market, which are acceptable to Islamic law as bonds play a major role in the economy in raising capital. The main objective of this paper is to examine the contemporary accounting regulatory issues on investment in Islamic bonds or Sukuk in Malaysia. Sukuk can be based on various Islamic contracts, namely Mudarabah, Murabahah, Musharakah, and Ijarah. Due to the growth in the Islamic financial market, namely the Islamic bonds, as well as the growing interest in Islamic banking and insurance, the need for specific accounting requirements that can accommodate these contracts is imperative. This paper is based on the rationale that for the Islamic financial market to prosper, it requires well regulated Islamic financial instruments, as well as appropriate accounting standards and guidelines in recording these instruments. Therefore, a well regulated Islamic financial market requires sound accounting and reporting standards for Islamic financial instruments that meet the requirements of Shari‘ah as well as being practical. In addition, this paper also highlights issues raised concerning the accounting practices in Islamic bonds investments.